H13-TiC pre-alloyed composite powder as well as preparation method and application thereof
Through the preparation method of H13-TiC pre-alloyed composite powder, vacuum smelting and smelting atomization technology are used to generate TiC enhanced phase in situ, and spherical composite powder is formed through plasma rotary electrode atomization technology, which solves the problem of uneven distribution of ceramic particles in traditional composite materials, achieves uniform distribution and efficient combination of TiC particles, and improves the performance of composite materials.
Patent Information
- Application Number
- CN202411955469.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-28
- Publication Date
- 2025-03-28
AI Technical Summary
In traditional H13 steel-based composite materials, the uneven mixing of ceramic particles and steel substrates, weak interface bonding, and poor dispersion, making it difficult to fully exert the excellent performance of ceramic particles.
The preparation method of H13-TiC pre-alloyed composite powder is adopted. Through vacuum smelting and smelting atomization technology, in-situ reaction is used to generate TiC enhanced phases, and spherical composite powder is formed through plasma rotary electrode atomization technology to ensure that the TiC particles are evenly distributed in the H13 steel matrix in nano or submicron sizes.
In powder metallurgy and additive manufacturing, the problems of uneven mixing of reinforced phase and matrix with traditional premixed powders, easy introduction of impurities, spherical damage, etc., achieving uniform distribution and efficient combination of TiC particles, and improving the performance of composite materials.
Smart Images

Figure CN119703045A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite powder preparation, and in particular relates to a H13-TiC pre-alloyed composite powder and a preparation method and application thereof. Background Art
[0002] As a medium-carbon hot working steel, H13 steel has become the most widely used hot working die steel at home and abroad due to its good toughness, hardenability and thermal fatigue resistance. Hot working dies are required in the production of most metal parts in the fields of aviation, rail transportation, automobiles, etc., such as aircraft engine blades, high-speed rail track fasteners and metal pads, automotive shaft parts and key components such as automotive differential gears. Hot working die steel is used to press metal or liquid metal heated to above the recrystallization temperature into workpieces. It is mainly used for hot forging dies, die casting dies, hot extrusion dies, etc. Since hot working die steel usually works at a higher temperature and needs to withstand the combined effects of thermal shock and thermal wear, extremely stringent requirements are placed on the performance of the hot working die material itself. The main failure modes of traditional hot working die steel are: (1) thermoplastic deformation, (2) thermal wear and (3) thermomechanical fatigue damage. At present, in order to improve the quality of hot working die steel and extend its service life, researchers have strengthened the matrix and surface of H13 steel based on alloy composition optimization (mainly Cr / Mo / V element regulation), microalloy strengthening (introduction of Si / W elements) to achieve secondary hardening of materials, and heat treatment process optimization, thereby improving toughness, wear resistance and high temperature fatigue performance. However, due to the requirements for the content of various alloy elements in the H13 steel base material, the use of composition optimization and heat treatment to strengthen the comprehensive performance of H13 steel has almost reached a bottleneck, and it is difficult to further significantly improve the performance of hot working die steel.
[0003] Studies have shown that ceramic particles such as TiC, TiB2, and WC with excellent wear resistance, corrosion resistance, high temperature resistance, and oxidation resistance can be introduced into the steel matrix by the addition method (mechanical alloying, mechanical mixing method), so as to realize the composite of the steel matrix and obtain ceramic particle reinforced steel matrix composite materials. The composite materials have the advantages of both metal materials and ceramic materials, overcome the problem of the mutual restriction of wear resistance and toughness of traditional wear-resistant materials, and have good thermal conductivity, wear resistance, and high temperature resistance. At present, the research on particle reinforced H13 steel matrix composite materials mainly focuses on the laser cladding of H13+TiC and H13+TiB2 mixed powders. Although TiC particles have stable high temperature performance, they will neither decompose nor react chemically with the H13 steel matrix at high temperature. However, the introduction of such ceramic particles by the addition method has problems such as poor wettability with the steel matrix, weak interface bonding, and poor dispersibility, which makes it difficult to give full play to the excellent intrinsic properties of such ceramic particles.
[0004] In-situ particle-reinforced metal matrix composites have become the mainstream research direction because of their advantages such as good interface bonding. The main preparation technologies at present are: fusion-casting, powder metallurgy (PM) and additive manufacturing (AM). Among them, powder metallurgy uses metal powder and reinforcement phase as raw materials, solidifies and sintered the uniformly mixed powder at a certain temperature, minimizes the segregation of alloy components, and eliminates coarse and uneven casting structure. Composite materials prepared by powder metallurgy have low interface reaction degree, fewer restrictions on the type of reinforcement, and the grain size of the composite material can be controlled. At the same time, mixing before sintering will make the distribution of reinforcement more uniform. Additive manufacturing technology is based on rapid prototyping technology. It uses computer technology to assist in slicing three-dimensional models, generate scanning paths, and use high-energy beams (lasers, electron beams) to quickly melt and solidify pre-alloyed powders and deposit them layer by layer to achieve the integrated forming of complex structural materials. This technology breaks the limitations of the traditional "casting-forging-machining" process and has significant advantages in forming components with complex and precise structures and narrow processing windows. It shows broad application prospects in application fields such as high-end equipment manufacturing such as aerospace, rail transportation, etc.
[0005] As a key raw material for advanced manufacturing, metal powder has become one of the research focuses in the field of powder metallurgy and additive manufacturing. Spherical metal powders prepared by atomization powder making technology (VIGA, EIGA, PREP, etc.) are widely used in powder metallurgy, additive manufacturing, etc. because of their advantages such as high sphericity, good fluidity, and low impurity and oxygen content. The above preparation technologies all use powder as the initial raw material, mix the matrix powder with the reinforcement phase powder by ball milling, and then form the composite material by powder metallurgy solidification sintering or additive manufacturing. However, in traditional research, the premixed powder prepared by ball milling has problems such as powder contamination, uneven mixing, and sphericity destruction, resulting in inclusions, internal defects, incomplete reaction of the reinforcement phase, and weak interface bonding between the reinforcement phase and the matrix in the prepared composite material, which limits the performance improvement effect of ceramic particles on the metal matrix. Summary of the invention
[0006] The purpose of the present invention is to provide a H13-TiC pre-alloyed composite powder and a preparation method and application thereof, so as to solve the technical problems of poor fluidity caused by uneven matrix powder and mixed powder, easy introduction of impurities and destruction of sphericity.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions: The invention discloses a H13-TiC pre-alloyed composite powder. The raw materials of the H13-TiC pre-alloyed composite powder include, by mass percentage, 0.5-5 wt.% of carbon powder, 3.5-15 wt.% of titanium material and 95%-80wt.% of H13 material. In the H13-TiC pre-alloyed composite powder, the content of in-situ self-generated TiC is 5-20 wt.%.
[0008] The present invention also discloses a method for preparing the above H13-TiC pre-alloyed composite powder, comprising the following steps: Weigh carbon powder, titanium material and H13 material as raw materials according to the mass percentage of claim 1; The H13 material, carbon powder and titanium material are sequentially placed in a melting furnace, vacuumed and then induction heated for melting, and after melting, the melt is poured into a mold to obtain an H13-TiC composite material ingot; After post-processing the H13-TiC composite material ingot, a H13-TiC consumable electrode rod is obtained; The H13-TiC consumable electrode rod is melted and atomized to obtain H13-TiC pre-alloyed composite powder.
[0009] Furthermore, the induction heating melting method is cold crucible suspension melting; the parameters of the induction heating melting are: magnetic induction heating frequency is 8~12 KHz; melting temperature is 1600~1800 ℃; melting time is 15~20 min.
[0010] Furthermore, the vacuum pressure is 4.5~5×10 -3 Pa.
[0011] Furthermore, iron foil is placed between the H13 material and the carbon powder; the purity of the iron foil is 99.9%.
[0012] Furthermore, the induction heating melting is repeated 2 to 3 times; The casting mold adopts a method of casting the melt into a graphite mold under vacuum.
[0013] Furthermore, the post-processing is to cut off the upper end gate and the bottom of the H13-TiC composite material ingot; the titanium material is sponge titanium or titanium powder; and the H13 material is an H13 steel ingot.
[0014] Furthermore, the smelting atomization method is plasma rotating electrode atomization; the parameters of the smelting atomization are: the working speed of the electrode rod is 22000~26000 rpm, the powder particle size collection interval is set to 45~150 μm, and the smelting atomization process is carried out under argon or helium protection.
[0015] The present invention also discloses the application of the H13-TiC pre-alloyed composite powder in 3D printing.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses an H13-TiC pre-alloyed composite powder. According to the component design, 0.5-5 wt.% of carbon powder, 3.5-15 wt.% of titanium material and 95%-80 wt.% of H13 material are adopted to form 5-20 wt.% of TiC in situ. The TiC is evenly distributed in an H13 steel matrix in a mesh shape with a nanometer or submicron size. The spherical composite powder solves many problems in powder metallurgy and additive manufacturing, such as uneven mixing of reinforcement phase and matrix raw materials, easy introduction of impurities, sphericity destruction, incomplete reaction of reinforcement phase particles in the prepared composite material, easy agglomeration, and the like.
[0017] The invention also discloses a preparation method of the above-mentioned H13-TiC pre-alloyed composite powder, which utilizes vacuum melting treatment to make carbon powder and titanium material react in situ to generate TiC reinforcement phase during the process, then utilizes plasma arc heating in the melting and atomization process to realize remelting of H13 steel matrix and TiC, and then forms H13-TiC pre-alloyed composite powder under centrifugal force and rapid solidification conditions; the method of the invention has the following advantages in forming TiC reinforcement phase: during the melting process, TiC particles have good wettability with steel (iron) liquid at high temperature (the wetting angle is about 40° at 1550°C), are easy to precipitate in situ from the H13 steel matrix, and are evenly distributed; secondly, the remelting and centrifugal atomization process makes the coarse primary TiC particles in the molten-cast H13-TiC composite material re-dissolve and precipitate, and the eutectic structure is eliminated, thereby ensuring that TiC is evenly distributed in the composite powder at nanometer scale. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a metallographic micrograph of the molten-cast structure of the H13-TiC composite material ingot of the present invention; Figure 2 is the X-ray diffraction spectrum of the H13-TiC pre-alloyed composite powder of the present invention; Figure 3 This is a surface morphology diagram of the H13-TiC pre-alloyed composite powder of the present invention; Among them: a- low magnification SEM morphology; b- high magnification SEM morphology of a single powder; Figure 4 This is a cross-sectional morphology diagram of the H13-TiC pre-alloyed composite powder of the present invention; Among them: a-SEM morphology of powder cross section; b-high magnification SEM morphology of TiC distribution in powder cross section. DETAILED DESCRIPTION
[0019] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0020] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0021] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0022] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0023] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0024] The invention provides an H13-TiC pre-alloyed composite powder. The raw materials of the H13-TiC pre-alloyed composite powder include, by mass percentage, 0.5-5 wt.% of carbon powder, 3.5-15 wt.% of titanium material and 95%-80 wt.% of H13 material, the sum of the mass percentages of the above components being 100%. Based on the original Ti and C content design, the in-situ self-generated TiC content in the finally obtained composite powder is 5-20 wt.%; wherein the titanium material is sponge titanium or titanium powder.
[0025] As attached Figure 4 As shown in the figure, TiC generated by in-situ reaction is evenly distributed in the H13 steel matrix in nanometer or submicron size. The average particle size of the original carbon powder is about 5 μm, and the purity is 99%; the average particle size of sponge titanium (or pure titanium powder) is about 10 mm (or 45 μm), and the purity is about 99.8%; the original H13 steel ingot is irregular, and the specific composition of each raw material is shown in the table below.
[0026] Table 1 Chemical composition of H13 steel (wt.%)
[0027] Table 2 Chemical composition of titanium sponge or titanium powder (wt.%)
[0028] The present invention also discloses a method for preparing the above H13-TiC pre-alloyed composite powder, comprising the following steps: Step 1: Weigh the raw materials According to the designed in-situ self-generated TiC content of 5-20 wt.%, weigh 0.5-5 wt.% of carbon powder, 3.5-15 wt.% of titanium sponge (or titanium powder), and 95%-80 wt.% of H13 steel ingot respectively according to the mass percentage. The sum of the mass percentages of the above raw materials is 100%; Step 2: Smelting Preparation The carbon powder weighed in step 1 is pre-pressed by a hydraulic press, and then the H13 steel ingot, carbon powder and sponge titanium (or titanium powder) are placed in a 20 kg melting furnace. In order to avoid premature contact and reaction between Fe (steel) and C element to form Fe-C compounds and affect the in-situ reaction of Ti-C, high-purity iron foil (purity 99.9%, size 0.02*150*150mm) is placed between the H13 steel ingot and sponge titanium (or titanium powder). The Fe element increment brought by the introduced high-purity iron foil is less than 0.06%. After the above preparations are correct, the melting furnace body is vacuumed; Step 3: Cold Crucible Magnetic Levitation Melting After the vacuum in step 2 is achieved, the raw materials are subjected to induction heating melting using a cold crucible suspension melting device, and the carbon powder reacts in situ with the titanium sponge or titanium powder at high temperature to generate a TiC reinforcement phase; in order to promote the in-situ reaction between the Ti-C elements during the melting process, the H13-TiC ingot obtained by the preliminary melting is remelted 2 to 3 times to ensure that the reaction between the raw materials is sufficient and uniform; after the melting is completed, the remelted melt is poured into a high-purity graphite mold with a size of Փ60 mm×600 mm in a vacuum atmosphere, and the mold is cooled to room temperature to obtain an H13-TiC composite material ingot; Step 4: Preparation of consumable electrode rods The top gate and bottom of the H13-TiC composite ingot were cut off to obtain a 60 mm × 400 mm rod, which was then machined according to the consumable electrode size requirements of PREP atomization powder making to finally obtain a 52 mm × 260 mm H13-TiC consumable electrode rod. Step 5: Preparation of spherical H13-TiC pre-alloyed composite powder The consumable electrode obtained in step 4 is melted and atomized by plasma rotating electrode atomization technology to finally obtain H13-TiC pre-alloyed composite powder.
[0029] The principle of the present invention is to transform the in-situ reaction-diffusion-growth mechanism of the reinforcement phase particles in the traditional in-situ self-generated TiC particle reinforced steel-based composite material into the supersaturated solid solution-nucleation-precipitation-growth mechanism of the reinforcement phase forming element (Ti-C). The specific implementation process is: with the help of the traditional smelting and casting process, the in-situ reaction of C and Ti elements is realized, so that TiC particles are precipitated in situ in the H13 steel melt, and the molten-cast H13-TiC composite material is initially obtained; then the consumable electrode rod made of the molten-cast H13-TiC composite material is melted, centrifugally atomized and rapidly solidified by atomization powder making technology (PREP). With the help of the rapid cooling and solidification process of the atomization process, the coarse primary TiC particles in the molten-cast structure are further refined and homogenized, and the eutectic structure is eliminated. Based on the above ideas, a spherical H13-TiC pre-alloyed composite powder containing nano- or submicron-sized TiC reinforcement phase is designed and prepared to solve the problems existing in the existing premixed powder system.
[0030] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0031] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0032] Example 1 A method for preparing H13-TiC pre-alloyed composite powder comprises the following steps: Step 1: Weigh the raw materials According to the designed in-situ self-generated TiC content of 5 wt.%, carbon powder 1.003 wt.%, titanium sponge 3.987 wt.%, H13 steel ingot 95 wt.%, were weighed according to mass percentage, and the sum of the mass percentages of the above raw materials is 100%; Step 2: Smelting Preparation The carbon powder weighed in step 1 was pre-pressed by a hydraulic press, and then the H13 steel ingot, carbon powder and sponge titanium were placed in a 20 kg melting furnace. In order to avoid premature contact and reaction between Fe (steel) and C element to form Fe-C compounds and affect the in-situ reaction of Ti-C, high-purity iron foil (purity 99.9%, size 0.02*150*150mm) was placed between the H13 steel ingot and sponge titanium (or titanium powder). The Fe element increment brought by the introduced high-purity iron foil was less than 0.06%. After the above preparations were correct, the melting furnace was vacuumed for 4.5×10 -3 Pa; Step 3: Cold Crucible Magnetic Levitation Melting After the vacuum in step 2 is up to standard, the raw materials are subjected to induction heating melting by using a cold crucible suspension melting device, and the carbon powder reacts in situ with the titanium sponge or titanium powder at high temperature to generate a TiC reinforcement phase; in order to promote the in situ reaction between the Ti-C elements during the melting process, the H13-TiC ingot obtained by the preliminary melting is remelted twice to ensure that the reaction between the raw materials is sufficient and uniform; after the melting is completed, the remelted melt is poured into a high-purity graphite mold with a size of Փ60 mm×600 mm in a vacuum atmosphere, and the mold is cooled to room temperature to obtain an H13-TiC composite material ingot; wherein, the parameters of the induction heating melting are: under the condition of 12KHz high-frequency magnetic field heating, the raw material is heated to 1650°C and melted for 15 min to ensure uniform melt reaction; Step 4: Preparation of consumable electrode rods The top gate and bottom of the H13-TiC composite ingot were cut off to obtain a 60 mm × 400 mm rod, which was then machined according to the consumable electrode size requirements of PREP atomization powder making to finally obtain a 52 mm × 260 mm H13-TiC consumable electrode rod. Step 5: Preparation of spherical H13-TiC pre-alloyed composite powder The consumable electrode obtained in step 4 is melted and atomized by plasma rotating electrode atomization technology to finally obtain H13-TiC pre-alloyed composite powder; wherein the parameters of melting and atomization are: the working speed of the electrode rod is 22000~26000rpm, the powder particle size collection interval is set to 45~150 μm, and the atomization process is carried out under argon or helium protection.
[0033] Example 2 A method for preparing H13-TiC pre-alloyed composite powder comprises the following steps: Step 1: Weigh the raw materials According to the designed in-situ self-generated TiC content of 10 wt.%, carbon powder 2.01 wt.%, titanium sponge 7.99 wt.%, H13 steel ingot 90 wt.%, were weighed according to mass percentage, and the sum of the mass percentages of the above raw materials is 100%; Step 2: Smelting Preparation The carbon powder weighed in step 1 was pre-pressed by a hydraulic press, and then the H13 steel ingot, carbon powder and sponge titanium were placed in a 20 kg melting furnace. In order to avoid premature contact and reaction between Fe (steel) and C element to form Fe-C compounds and affect the in-situ reaction of Ti-C, high-purity iron foil (purity 99.9%, size 0.02*150*150mm) was placed between the H13 steel ingot and sponge titanium (or titanium powder). The Fe element increment brought by the introduced high-purity iron foil was less than 0.06%. After the above preparations were correct, the melting furnace was vacuumed to a vacuum degree of 4.5~5×10 -3 After Pa, the next step of induction melting preparation is carried out; Step 3: Cold Crucible Magnetic Levitation Melting After the vacuum in step 2 is up to standard, the raw materials are subjected to induction heating melting by using a cold crucible suspension melting device, and the carbon powder reacts in situ with the titanium sponge or titanium powder at high temperature to generate a TiC reinforcement phase; in order to promote the in situ reaction between the Ti-C elements during the melting process, the H13-TiC ingot obtained by the preliminary melting is remelted twice to ensure that the reaction between the raw materials is sufficient and uniform; after the melting is completed, the remelted melt is poured into a high-purity graphite mold with a size of Փ60 mm×600 mm in a vacuum atmosphere, and the mold is cooled to room temperature to obtain an H13-TiC composite material ingot; wherein, the parameters of the induction heating melting are: under the condition of 12KHz high-frequency magnetic field heating, the raw material is heated to 1650°C and melted for 15 min to ensure uniform melt reaction; Step 4: Preparation of consumable electrode rods The top gate and bottom of the H13-TiC composite ingot were cut off to obtain a 60 mm × 400 mm rod, which was then machined according to the consumable electrode size requirements of PREP atomization powder making to finally obtain a 52 mm × 260 mm H13-TiC consumable electrode rod. Step 5: Preparation of spherical H13-TiC pre-alloyed composite powder The consumable electrode obtained in step 4 is melted and atomized by plasma rotating electrode atomization technology to finally obtain H13-TiC pre-alloyed composite powder; wherein the parameters of melting and atomization are: the working speed of the electrode rod is 22000~26000rpm, the powder particle size collection interval is set to 45~150 μm, and the atomization process is carried out under argon or helium protection.
[0034] Example 3 A method for preparing H13-TiC pre-alloyed composite powder comprises the following steps: Step 1: Weigh the raw materials According to the designed in-situ self-generated TiC content of 15 wt.%, carbon powder 3.01 wt.%, titanium sponge 11.99 wt.%, H13 steel ingot 85 wt.%, were weighed according to mass percentage, and the sum of the mass percentages of the above raw materials is 100%; Step 2: Smelting Preparation The carbon powder weighed in step 1 was pre-pressed by a hydraulic press, and then the H13 steel ingot, carbon powder and sponge titanium were placed in a 20 kg melting furnace. In order to avoid premature contact and reaction between Fe (steel) and C element to form Fe-C compounds and affect the in-situ reaction of Ti-C, high-purity iron foil (purity 99.9%, size 0.02*150*150mm) was placed between the H13 steel ingot and sponge titanium (or titanium powder). The Fe element increment brought by the introduced high-purity iron foil was less than 0.06%. After the above preparations were correct, the melting furnace was vacuumed to a vacuum degree of 4.5~5×10 -3 After Pa, the next step of induction melting preparation is carried out; Step 3: Cold Crucible Magnetic Levitation Melting After the vacuum in step 2 is up to standard, the raw materials are subjected to induction heating melting by using a cold crucible suspension melting device, and the carbon powder reacts in situ with the titanium sponge or titanium powder at high temperature to generate a TiC reinforcement phase; in order to promote the in situ reaction between the Ti-C elements during the melting process, the H13-TiC ingot obtained by the preliminary melting is remelted twice to ensure that the reaction between the raw materials is sufficient and uniform; after the melting is completed, the remelted melt is poured into a high-purity graphite mold with a size of Փ60 mm×600 mm in a vacuum atmosphere, and the mold is cooled to room temperature to obtain an H13-TiC composite material ingot; wherein, the parameters of the induction heating melting are: under the condition of 12KHz high-frequency magnetic field heating, the raw material is heated to 1750°C and melted for 15 min to ensure uniform melt reaction; Step 4: Preparation of consumable electrode rods The top gate and bottom of the H13-TiC composite ingot were cut off to obtain a 60 mm × 400 mm rod, which was then machined according to the consumable electrode size requirements of PREP atomization powder making to finally obtain a 52 mm × 260 mm H13-TiC consumable electrode rod. Step 5: Preparation of spherical H13-TiC pre-alloyed composite powder The consumable electrode obtained in step 4 is melted and atomized by plasma rotating electrode atomization technology to finally obtain H13-TiC pre-alloyed composite powder; wherein the parameters of melting and atomization are: the working speed of the electrode rod is 22000~26000rpm, the powder particle size collection interval is set to 45~150 μm, and the atomization process is carried out under argon or helium protection.
[0035] Example 4 A method for preparing H13-TiC pre-alloyed composite powder comprises the following steps: Step 1: Weigh the raw materials According to the designed in-situ self-generated TiC content of 20 wt.%, carbon powder 4.01 wt.%, titanium sponge 15.99 wt.%, H13 steel ingot 80 wt.%, were weighed respectively according to mass percentage, and the sum of the mass percentages of the above raw materials is 100%; Step 2: Smelting Preparation The carbon powder weighed in step 1 was pre-pressed by a hydraulic press, and then the H13 steel ingot, carbon powder and sponge titanium were placed in a 20 kg melting furnace. In order to avoid premature contact and reaction between Fe (steel) and C element to form Fe-C compounds and affect the in-situ reaction of Ti-C, high-purity iron foil (purity 99.9%, size 0.02*150*150mm) was placed between the H13 steel ingot and sponge titanium (or titanium powder). The Fe element increment brought by the introduced high-purity iron foil was less than 0.06%. After the above preparations were correct, the melting furnace was vacuumed to a vacuum degree of 4.5~5×10 -3 After Pa, the next step of induction melting preparation is carried out; Step 3: Cold Crucible Magnetic Levitation Melting After the vacuum in step 2 is up to standard, the raw materials are subjected to induction heating melting by using a cold crucible suspension melting device, and the carbon powder reacts in situ with the titanium sponge or titanium powder at high temperature to generate a TiC reinforcement phase; in order to promote the in situ reaction between the Ti-C elements during the melting process, the H13-TiC ingot obtained by the preliminary melting is remelted twice to ensure that the reaction between the raw materials is sufficient and uniform; after the melting is completed, the remelted melt is poured into a high-purity graphite mold with a size of Փ60 mm×600 mm in a vacuum atmosphere, and the mold is cooled to room temperature to obtain an H13-TiC composite material ingot; wherein, the parameters of the induction heating melting are: under the condition of 12KHz high-frequency magnetic field heating, the raw material is heated to 1750°C and melted for 20 minutes to ensure uniform melt reaction; Step 4: Preparation of consumable electrode rods The top gate and bottom of the H13-TiC composite ingot were cut off to obtain a 60 mm × 400 mm rod, which was then machined according to the consumable electrode size requirements of PREP atomization powder making to finally obtain a 52 mm × 260 mm H13-TiC consumable electrode rod. Step 5: Preparation of spherical H13-TiC pre-alloyed composite powder The consumable electrode obtained in step 4 is melted and atomized by plasma rotating electrode atomization technology to finally obtain H13-TiC pre-alloyed composite powder; wherein the parameters of melting and atomization are: the maximum working speed of the electrode rod is 30000 rpm, the powder particle size collection range is set to 45~150 μm, and the atomization process is carried out under argon or helium protection.
[0036] Figure 1 This is the metallographic microstructure of the H13-TiC composite material ingot sample prepared in the present invention; it can be seen that the in-situ self-generated TiC particles are nearly spherical and evenly distributed in the H13 steel matrix, and the average particle size is about 5-10 μm.
[0037] Figure 2 This is the X-ray diffraction spectrum of the spherical H13-TiC pre-alloyed composite powder prepared in situ of the present invention; it can be seen that the composite powder phase is mainly composed of ferrite matrix and in-situ self-generated TiC, without other impurity phases, indicating that the powder purity is relatively high.
[0038] Figure 3 The surface morphology of the spherical H13-TiC pre-alloyed composite powder prepared in situ according to the present invention; Figure 3 (a) It can be seen that the H13-TiC pre-alloyed composite powder prepared by the rotating electrode atomization method has a high sphericity and no satellite powder; Figure 3 (b) It can be seen that the single powder has a high sphericity and there are dendrite morphology characteristics on the surface of the powder particles. This is due to the preferential solidification area characteristics formed by the non-equilibrium solidification of the molten droplets under rapid cooling conditions during the rotating electrode atomization process.
[0039] Figure 4 The cross-sectional morphology of the spherical H13-TiC pre-alloyed composite powder prepared in situ according to the present invention; Figure 4 (a) It can be seen that the powder cross section has a uniform structure and a smooth and finished morphology. Figure 4 (b) It can be seen that micro-nano TiC particles distributed in a continuous network can be observed in the core of the powder cross section.
[0040] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A H13-TiC pre-alloyed composite powder, characterized in that: In terms of mass percentage, the raw materials of the H13-TiC pre-alloyed composite powder include: 0.5-5 wt.% of carbon powder, 3.5-15 wt.% of titanium material and 95%-80 wt.% of H13 material; In the H13-TiC pre-alloyed composite powder, the content of in-situ self-generated TiC is 5-20 wt.%.
2. The method for preparing a H13-TiC pre-alloyed composite powder according to claim 1, characterized in that: The following steps are involved: Weigh carbon powder, titanium material and H13 material as raw materials according to the mass percentage of claim 1; The H13 material, carbon powder and titanium material are sequentially placed in a melting furnace, vacuumed and then induction heated for melting, and after melting, the melt is poured into a mold to obtain an H13-TiC composite material ingot; After post-processing the H13-TiC composite material ingot, a H13-TiC consumable electrode rod is obtained; The H13-TiC consumable electrode rod is melted and atomized to obtain H13-TiC pre-alloyed composite powder.
3. The method for preparing a H13-TiC pre-alloyed composite powder according to claim 2, characterized in that: The induction heating melting method is cold crucible suspension melting; the parameters of the induction heating melting are: magnetic induction heating frequency is 8-12 KHz; melting temperature is 1600-1800°C; melting time is 15-20 min.
4. The method for preparing a H13-TiC pre-alloyed composite powder according to claim 2, characterized in that: The vacuum pressure is 4.5~5×10 -3 Pa.
5. The method for preparing a H13-TiC pre-alloyed composite powder according to claim 2, characterized in that: Iron foil is placed between the H13 material and the carbon powder; the purity of the iron foil is 99.9%.
6. The method for preparing a H13-TiC pre-alloyed composite powder according to claim 2, characterized in that: The induction heating melting is repeated 2 to 3 times; The casting mold adopts a method of casting the melt into a graphite mold under vacuum.
7. The method for preparing a H13-TiC pre-alloyed composite powder according to claim 2, characterized in that: The post-processing is to cut off the upper end gate and the bottom of the H13-TiC composite material ingot; the titanium material is sponge titanium or titanium powder; and the H13 material is H13 steel ingot.
8. The method for preparing a H13-TiC pre-alloyed composite powder according to claim 2, characterized in that: The smelting atomization method is plasma rotating electrode atomization; the parameters of the smelting atomization are: the working speed of the electrode rod is 22000~26000 rpm, and the powder particle size collection range is set to 45~150 μm.
9. The method for preparing a H13-TiC pre-alloyed composite powder according to claim 8, characterized in that: The smelting atomization process is carried out under the protection of argon or helium.
10. Application of the H13-TiC pre-alloyed composite powder described in claim 1 in 3D printing.